2000
DOI: 10.1128/iai.68.12.6542-6553.2000
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of the scl Gene Encoding a Group A Streptococcus Extracellular Protein Virulence Factor with Similarity to Human Collagen

Abstract: Group A Streptococcus (GAS) expresses cell surface proteins that mediate important biological functions such as resistance to phagocytosis, adherence to plasma and extracellular matrix proteins, and degradation of host proteins. An open reading frame encoding a protein of 348 amino acid residues was identified by analysis of the genome sequence available for a serotype M1 strain. The protein has an LPATGE sequence located near the carboxy terminus that matches the consensus sequence (LPXTGX) present in many gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
218
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 155 publications
(224 citation statements)
references
References 58 publications
5
218
1
Order By: Relevance
“…All of these proteins are expressed on the GAS cell surface. With the exception of the streptococcal collagen-like protein-2, which was described very recently but not yet characterized in pathogenesis studies, all of these GAS proteins are virulence determinants in one or more model systems (13,43,(47)(48)(49). Involvement in pathogenesis was not studied, but two lines of evidence suggest that some of the 12 proteins we characterized participate in host-pathogen interactions, broadly defined.…”
Section: Implications For Pathogenesis and Development Of Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these proteins are expressed on the GAS cell surface. With the exception of the streptococcal collagen-like protein-2, which was described very recently but not yet characterized in pathogenesis studies, all of these GAS proteins are virulence determinants in one or more model systems (13,43,(47)(48)(49). Involvement in pathogenesis was not studied, but two lines of evidence suggest that some of the 12 proteins we characterized participate in host-pathogen interactions, broadly defined.…”
Section: Implications For Pathogenesis and Development Of Therapeuticsmentioning
confidence: 99%
“…More than 50 extracellular proteins with this motif have been described in Gram-positive bacteria, and many of them are virulence factors (38). For example, in GAS this motif is present in M protein, M-like proteins, C5a peptidase, GRAB protein, serum opacity factor, a fibronectin-binding protein, streptococcal protective antigen, and two collagen-like proteins (13,43,(47)(48)(49). All of these proteins are expressed on the GAS cell surface.…”
Section: Implications For Pathogenesis and Development Of Therapeuticsmentioning
confidence: 99%
“…22 Inasmuch as strain SF370 is genetically distinct from the great majority of strains responsible for contemporary infections caused by M1 strains, and is less virulent, we hypothesized that acquisition of novel genetic elements had created an unusually successful clone of serotype M1. 47,48 To test this hypothesis, we sequenced the genome of a strain that is genetically representative of organisms responsible for contemporary episodes of M1 infections. Genome sequencing, DNA-DNA microarray analysis, and high-throughput single nucleotide polymorphism analysis revealed that this clone evolved from an ancestral strain through a complex series of LGT episodes.…”
Section: Molecular Mechanisms Underlying the Emergence Of Severe Gas mentioning
confidence: 99%
“…Amongst the surface-exposed proteins more recently proposed as virulence factors in GAS are the collagen-like proteins Scl1 and Scl2, also known as SclA and SclB (Lukomski et al, 2000(Lukomski et al, , 2001Rasmussen et al, 2000;Whatmore, 2001). Both streptococcal and human collagens form triple helices (Mohs et al, 2007), leading to the hypothesis that streptococcal collagens could be involved in the production of antibodies that cross-react with host collagens and may play a role in streptococcal autoimmune disease (Xu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%